Age Structure Effects and Consumption in Norway, 1968(3) - 1998(4) - Solveig K. Erlandsen (Norges Bank, 2003)
In this paper the effects of a changing age distribution on aggregate consumption are analysed. This is done by estimating a Norwegian consumption function which controls for age structure effects. The model is estimated on quarterly time series data from 1968(3) to 1998(4). The results show that changes in the age composition affect aggregate consumption significantly, giving support to the predictions of the Life Cycle Hypothesis that young adults and old persons have a higher average propensity to consume than the middle-aged. The consumption model encompasses a model which does not control for age composition effects.
hdl:11250/2498627
Keywords: C22; E21; J1; 330; demography; consumption; time series models